Heat integrated resource conservation networks without mixing prior to heat exchanger networks - Tan, Y.; Ng, D.; Foo, D.; El-Halwagi, M.; Samyudia, Yudi (Elsevier Ltd, 2014)
This paper presents a generic approach for the synthesis of heat integrated resource conservation networks (HIRCNs) of the fixed flow rate problem, where process sources linked directly to process sinks without any prior mixing. The mixed integer non-linear program (MINLP) formulation complemented by floating pinch concept was developed to determine the optimum fresh material resources as well as hot and cold energy utilities. The proposed approach is applicable for both concentration- and property-based direct reuse/recycle system with variable operating parameters (i.e. flow rates, temperatures and properties). Three literature case studies are solved to illustrate the proposed approach. © 2014 Elsevier Ltd. All rights reserved.